A pilot study on clinicopathological features and intestinal microflora changes in colorectal cancer patients born over a nine-year period encompassing three years before and after the Great Chinese famine. (April 2019) - Li, Jiante; Wei, Zhiliang; Cao, Shougen; Tan, Xiaojie; Liu, Shanglong; Yao, Zengwu; Sun, Teng; Li, Yi; Zhang, Dongfeng; Zhou, Yanbing
Highlights: We present a study on the impact of energy restriction on diversity within the gut microbiome and how this relates to colorectal cancer in a Chinese population. Our study postulate that early life energy restriction influences the development and subsequent composition of the gut microbiome, which in turn influences the severity of outcomes after CRC diagnosis. We have used a cohort of individuals born in the three years prior to the great leap forward famine (GLFF), during the GLFF and in the three years after the GLFF. The study uses a unique, population wide event to identify the impact of energy restriction during early life development. Abstract: Background: Exposure to energy restriction during childhood is associated with a lower risk of developing colorectal cancer (CRC). To date, the association between this critical period of growth and prognosis of CRC has rarely been investigated. Changes in microbiota and epigenetic dysregulation may be key underlying mechanisms. Methodology: Tissues collected from patients born between 1956 and 1964 were grouped based on time-period. The differences in overall survival among patients from the three time-periods were examined via univariate analysis. The 16S rRNA gene sequencing approach was to determine differences in microbiota among the groups. Samples were randomly selected to detect BRAF mutations, microsatellite instability (MSI) and promoter CpG island methylator phenotype (CIMP) status. The chi-square test was to assess the relationship between alterations in these molecules and microbiota differences. Results: Patients from the three groups differed in terms of location of CRC (P = 0.034) and carcinoembryonic antigen (CEA) level (P = 0.036). A survival advantage was observed in the famine group compared with the other two groups. Fusobacterium nucleatum, Bacteroides fragilis and Escherichia coli were more abundant in the two comparing groups. Abundance of B. fragilis was associated with BRAF mutations, microsatellite instability (MSI) and abundance of E. coli . Moreover, the incidence of CIMP and MSI was higher in patients with greater abundance of F. nucleatum . Conclusions: Limitation of energy intake during childhood may affect the composition of gut microbiota, resulting in persistent epigenetic changes that subsequently influence the prognosis of patients with CRC.